Estudo fitoquímico e atividade biológica de Lupinus lanatus - Tiburski Neto, Alexandre (2011)
As a part of our ongoing search of new bioactive secondary metabolites of plant origin, the aerial parts of Lupinus lanatus were subjected to phytochemical investigation. Lupinus genus, belonging to the family of Leguminosae (Fabaceae), is widely distributed in south and western North America, in the Mediterranean region and Africa, with approximately 600 species. In Rio Grande do Sul, Brazil, the genus is represented by 13 species, among them, L. lanatus. This is a small shrub native to South America, mainly south Brazil (Rio Grande do Sul), Uruguai, Paraguai and Argentine. In Rio Grande do Sul, L. lanatus is called tremoço, and it is used in folk medicine as an antidiabetic, antifungal, antitumor and antioxidant agent. Quinolizidine alkaloids, such as lupanine, multiflorine, sparteine and argirine, are widely distributed in plants of the genus. Their biological effects, as antiarrhythmic, hypoglycemic, hypotensive, depressing CNS, hallucinogenic and respiratory stimulant activities, among others, has been studied previously. In the present paper, we describe the isolation and structural elucidation of a new quinolizidine alkaloid, lanatine A together with 13-α-cinnamoyloxylupanine, and hydroxylupanine from the leaves, and (-)multiflorine and (-)13-α-cis-tigloyloxymultiflorine from the seeds of L. lanatus.